Enhanced pre-processing and parameterization process of generic code clone detection model for clones in Java applications - Nur Nadzirah, Mokhtar; Mubarak-Ali, Al-Fahim; Mohd Azwan, Mohamad Hamza (The Science and Information (SAI) Organization Limited, 2020)
Code clones are repeated source code in a program. There are four types of code clone which are: Type 1, Type 2, Type 3 and Type 4. Various code clone detection models have been used to detect code clone. Generic Code Clone model is a model that consists of a combination of five processes in detecting code clone from Type-1 until Type-4 in Java Applications. The five processes are Pre-processing, Transformation, Parameterization, Categorization and Match Detection process. This work aims to improve code clone detection by enhancing the Generic Code Clone Detection (GCCD) model. Therefore, the Preprocessing and Parameterization process is enhanced to achieve this aim. The enhancement is to determine the best constant and weightage that can be used to improve the code clone detection result. The code clone detection result from the proposed enhancement shows that private with its weightage is the best constant and weightage for the Generic Code Clone Detection Model.